2014
DOI: 10.1136/bjophthalmol-2013-304436
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy following orbital exenteration

Abstract: Orbital exenteration is a physically debilitating procedure that may be a necessity in the management of orbital malignancy. It requires a sensitive multidisciplinary approach, both preoperatively and postoperatively. Providing life expectancy information for patients during preoperative counselling is pertinent to informed consent and in addressing patients' expectations. A retrospective review from one tertiary care centre was undertaken for a cohort of patients who were exenterated for orbital malignancy be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 14 publications
5
19
0
Order By: Relevance
“…This could be due to the distribution of patient age group in our study, consisting equal number of children and adults with high occurrence of retinoblastoma responsible for exenteration in childhood. We observed orbital tumor as the second most common primary site of tumor responsible for exenteration, which is similar with the findings of other studies (3, 4,8). …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This could be due to the distribution of patient age group in our study, consisting equal number of children and adults with high occurrence of retinoblastoma responsible for exenteration in childhood. We observed orbital tumor as the second most common primary site of tumor responsible for exenteration, which is similar with the findings of other studies (3, 4,8). …”
Section: Discussionsupporting
confidence: 92%
“…The most common indication for exenteration in our study was retinoblastoma (32.1%), and this was discordant with other literature findings (3 4, 8, 9) which reported that eyelid tumor was the most common etiology responsible for exenteration. This could be due to the distribution of patient age group in our study, consisting equal number of children and adults with high occurrence of retinoblastoma responsible for exenteration in childhood.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…42,43 Currently, the decision to proceed with conservation of the globe is individualized to the patient based on tumor location, tumor behavior, tumor subtype, reconstruction goals, and patient preference. 18,20,[42][43][44][45] The roles of and interplay between 'globe sparing' surgery and targeted therapy in the treatment of periorbital skin cancer require further study. The inconsistent and in select cases short duration of follow-up is a significant limitation of the study, and therefore the long-term survival data must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“… 12 15 Despite evidence that exenteration can achieve surgical cure, 14 , 16 , 17 it is associated with significant morbidity and deformity. 15 , 18 20 …”
Section: Discussionmentioning
confidence: 99%